2019
DOI: 10.1002/jcp.28410
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐30a inhibits the liver cell proliferation and promotes cell apoptosis through the JAK/STAT signaling pathway by targeting SOCS‐1 in rats with sepsis

Abstract: Sepsis is a systemic inflammatory response that may be induced by trauma, infection, surgery, and burns. With the aim of discovering novel treatment targets for sepsis, this current study was conducted to investigate the effect and potential mechanism by which microRNA‐30a (miR‐30a) controls sepsis‐induced liver cell proliferation and apoptosis. Rat models of sepsis were established by applying the cecal ligation and puncture (CLP) method to simulate sepsis models. The binding site between miR‐30a and suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Monitoring blood D-lactate levels can reflect intestinal permeability changes and the extent of damage (34). Studies have also revealed a higher content of TNF-α, IL-6, and IL-8 in sepsis serum than in serum from sham-operated rats (14,35), which was consistent with the findings of the present study. In addition to serum, the levels of TNF-α, IL-6, and IL-8 have also been reported to be increased in the intestines (36).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Monitoring blood D-lactate levels can reflect intestinal permeability changes and the extent of damage (34). Studies have also revealed a higher content of TNF-α, IL-6, and IL-8 in sepsis serum than in serum from sham-operated rats (14,35), which was consistent with the findings of the present study. In addition to serum, the levels of TNF-α, IL-6, and IL-8 have also been reported to be increased in the intestines (36).…”
Section: Discussionsupporting
confidence: 93%
“…JAK/STAT signaling pathway has been shown related to the release of various cytokines and inflammatory mediators and involved in the regulation of immune response in sepsis (7,8). Some other miRNAs, as miRNA-30a and miR-155 were also reported regulated sepsis-induced liver injury through regulating JAK/STAT signaling pathway (14,15). In the present study, we confirmed the relationship between miR-181b, JAK/STAT signaling pathway on influencing permeability of BBB.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…JEV infection downregulates the expression of miRNA miR-432, which directly targets the suppressor of cytokine signaling protein 5 (SOCS5) and manipulates the JAK-STAT1 signaling cascade (Sharma et al, 2016). The miR-30 family has been reported to target SOCS family members and manipulate the JAK/STAT signaling pathway (Zou et al, 2017;Ma et al, 2018;Yuan et al, 2019). In this study, we showed that PEDV infection suppressed miR-30c-5p expression, which was conversely related to SOCS1 expression during PEDV infection (Figure 4).…”
Section: Discussionmentioning
confidence: 66%
“…In this study, we showed that PEDV infection suppressed miR-30c-5p expression, which was conversely related to SOCS1 expression during PEDV infection (Figure 4). Just as other members of miR-30, miR-30c-5p specifically targeted the 3 ′ UTR of SOCS1 and inhibited SOCS1 expression (Kobayashi et al, 2012;Ma et al, 2018;Yuan et al, 2019) (Figure 4). However, the mechanism of PEDV decreasing miR-30a-5p remains unclear and deserves further study.…”
Section: Discussionmentioning
confidence: 97%